A lignin‐based flame retardant for improving fire behavior and biodegradation performance of polybutylene succinate. (30th September 2018) - Chen, Si; Lin, Shichao; Hu, Yan; Ma, Meng; Shi, Yanqin; Liu, Junding; Zhu, Feng; Wang, Xu
Abstract : The fast biodegradation rate and inflammability of polybutylene succinate (PBS) severely restrict its applications in many areas. To solve the above problems and broaden its applications, herein, a halogen‐free flame retardant (CP‐lignin) based on lignin was successfully synthesized. After adding 30 wt% CP‐lignin into PBS, the peak heat release rate and total heat release of PBS are remarkably reduced by 27 and 31%, respectively. Additionally, the higher char yield was beneficial to improving the flame retardant properties of PBS. After adding 10 wt% CP‐lignin, the ratio of weight loss is reduced by about 33%, and the ratio of weight loss is decreased gradually as the CP‐lignin loading increases. This research provides a reasonably way to make full use of the lignin and to broaden the application of PBS. At the same time, it also provides a new idea for the production and preparation of completely biodegradable materials.